2023
DOI: 10.1002/hep.32792
|View full text |Cite
|
Sign up to set email alerts
|

Steatosis, HBV‐related HCC, cirrhosis, and HBsAg seroclearance: A systematic review and meta‐analysis

Abstract: Background and Aims: NAFLD and chronic hepatitis B (CHB) infection are common etiologies of HCC. The impact of hepatic steatosis on HCC in CHB, as well as its relationship with the development of cirrhosis, fibrosis, and HBsAg seroclearance, remains controversial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
55
6

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(63 citation statements)
references
References 49 publications
2
55
6
Order By: Relevance
“…factors, including IR; however, genetic factors are also known to be clinically relevant, and PNPLA3 SNP is wellknown to be a disease-sensitive gene, and is suggested to have an IR-independent clinical role in the development of NAFLD (19). In agreement with a previous report (18), the presence of HS was associated with the development of HCC in HBV-infected patients. In addition, our present results also suggest that abnormal HOMA-IR values and PNPLA3 SNPs could relate to the presence of HS and development of HCC.…”
Section: Figure 6 the Sub-analysis Of The Association Of Homeostasis ...supporting
confidence: 89%
See 1 more Smart Citation
“…factors, including IR; however, genetic factors are also known to be clinically relevant, and PNPLA3 SNP is wellknown to be a disease-sensitive gene, and is suggested to have an IR-independent clinical role in the development of NAFLD (19). In agreement with a previous report (18), the presence of HS was associated with the development of HCC in HBV-infected patients. In addition, our present results also suggest that abnormal HOMA-IR values and PNPLA3 SNPs could relate to the presence of HS and development of HCC.…”
Section: Figure 6 the Sub-analysis Of The Association Of Homeostasis ...supporting
confidence: 89%
“…HBV-infection is a well-recognized risk factor for the development of hepatocellular carcinoma (HCC) (15)(16)(17), and concomitant HS is suggested to increase the risk of developing HCC in HBV-infected patients (18). PNPLA3 SNP and IR have been suggested to play cooperative roles in the development of fatty liver disease (19,20); however, it is still uncertain whether PNPLA3 SNP is related to the development of HCC in HBV-infected patients (21)(22)(23)(24)(25).…”
mentioning
confidence: 99%
“…One of the plausible explanations for the above conflicting results may be the heterogeneous study populations enrolled in each study; CHB patients fulfilling the indication of the liver biopsy were expected to have higher disease severity and represented a minority among the broad disease spectrum of CHB and MAFLD, leading to the diverse results. This speculation was supported by a meta-analysis that showed no significant association between steatosis and HCC after excluding those with biopsy-proven fatty liver 21 . Another factor is the influence of the co-existing metabolic dysfunction in patients with MAFLD, including obesity or DM, which are also the established risk factors for HCC occurrence in CHB [35][36][37] .…”
Section: Inconclusive Results For Mafld and Risk Of Hbv-related Hccmentioning
confidence: 93%
“…A retrospective cohort study on a liver biopsy cohort of 270 CHB patients showed concurrent fatty liver was an independent risk factor of HCC (adjusted hazard ratio [HR] 7.27, 95% CI 1.52 -34.76, p = 0.013) 28 ; another study of 1089 CHB patients with available liver histology found NASH was independently associated with a higher risk of HCC 27 ; recently, the same cohort using the new criteria of MAFLD defined by histology revealed MAFLD was associated with poorer HCC-free survival (adjusted HR 1.93, 95% CI 1.17 -3.21); however, steatohepatitis did not increase the risk of HCC among patients with MAFLD, indicating metabolic dysfunction rather than steatosis per se as the key role in the hepatocarcinogenesis 34 . A recent meta-analysis showed that the presence of fatty liver, especially biopsy-proven steatosis, was associated with an increased risk of HCC in CHB patients 21 .…”
Section: Inconclusive Results For Mafld and Risk Of Hbv-related Hccmentioning
confidence: 99%
See 1 more Smart Citation